Status And Development of Wall Materials in China - Wei, Shuang (Transactions on Engineering and Technology Research, 2024)
New wall materials are advanced materials with many excellent properties such as lightweight, high strength, sound absorption, heat preservation, energy saving and environmental protection, and represent the development trend of advanced wall materials technology. Based on this, this paper firstly introduces the development status of China and western countries, then shows the characteristics, types, uses and development status of new wall materials developed in China, and finally discusses the problems that need to be solved in its development. The results of the study show that: Western countries have established appropriate policies and relatively environmentally friendly building environments, and China is striving to develop new wall materials and shift to green buildings. Therefore, new wall materials will become the preferred building materials in the future, and new wall materials have their own advantages and disadvantages, which need to be combined with a variety of conditions for selection and further research and development.